Analysis of Grice’s Violation Maxim in Mark Twain’s Novel the Adventure of Tom Sawyer (1993) - Robby Anouvali Taufiq; Leni Marlina (Universitas Negeri Padang, 2022)
Theory cooperative principle work as a guideline that instructs people to interact with one another constructively and cooperatively. Grice P. is the one who wrote and delivered it in 1975. The cooperative principle is divided into four types of maxims which are quantity (amount of information), quality (the validity of information), relation (relatability of information), and manner (information delivery). However, there are times when the speaker tries to misguide the listener, and it is called a violation of the maxim principle. It is a maxim created to trick the listener into believing something false while the listener is ignorant of it. Additionally, it creates a problem for linguists since implicature, one of the issues in the field of linguistics, notably pragmatics, is linked to the violation. It happens not only in real-world conversation but also in literary work for example novels. This research examines the maxims that the protagonist of the novel The Adventures of Tom Sawyer (1993) violated. A famous novel by famous American writer Mark Twain which tells about Tom Sawyer’s misbehavior and his escapade. Random data sampling is used to collect the data from the source of data to determine the association between one maxim violation and another. The data was collected from statements made by Thomas Sawyer, the book's main character, and various supporting characters in 9 of the novel's 35 chapters. To examine the data from the novel The Adventure of Tom Sawyer, Grice's cooperative principle theory from 1975 is employed, as well as Tupan and Natalia's maxim violation indicator (2008). This analysis found that out of 360 total utterances in 9 chapters, there are only three maxim violations in The Adventure of Tom Sawyer: the violation of quality maxim, relation maxim, and number maxim. 14 infractions of 18 utterances, driven by two indicators, represent 66 percent of the quality maxim violation (lies and denies something). The quantity maxim shows 10% occurrence (2 violations out of 18 utterances dominated by two indicators). In comparison, the relation maxim shows 24 percent occurrence (5 violations out of 18 utterances with each utterance dominating all of the indicators (unmatched topic, avoid something, hides a fact, and the wrong causality)) (uninformative, and talk too much). As a result, The Adventure of Tom Sawyer contains claims that mostly violate the quality and relational maxims.